Knowledge, attitude and practice towards breastfeeding among mothers in Kuantan, Malaysia - Al-Kubaisi, Muna Khaleel Dheyab; Awang, Mokhtar; Ismail, Hamizah; Akter, Seikh Farid Uddin; Mansoor, Nargis (2013)
Background Breastfeeding is the natural route for feeding the newborn that has a lot of documented advantages upon maternal and child health. All over the world, higher employment rates in recent years among women have had an impact on infant breastfeeding. Many national and international projects had been established to promote the breastfeeding that might reflect its effect on the attitude of the mothers and the community. The objective of this study was to evaluate practice, knowledge and attitude to breastfeeding among women in Kuantan the capital of Pahang state, the largest state in the peninsula of Malaysia. Methodology A cross sectional study was carried out between 23rd February 2011 and 22nd January 2013. A total of 222 women with children aged between 2- 3 years attending the clinic in Hospital Tengku Ampuan Afzan and three primary health care centres were randomly selected. Women with the targeted study group were interviewed. Information regarding participants' demographics, knowledge, attitude and practice towards breastfeeding were obtained through a structured questionnaire. Results The demographic results of our sample (n=222) reveal mother`s age ranging between 20 and 46 years old in which the majority (48.2%, n=107) with secondary school qualification and about two third (68%, n=151) with household income between 1000-3000RM (medium class). Employment with full time was 51.1% and 38.3% house wives. Regarding the practice; establishing breastfeeding is delayed for more than 24 hour in 45% of them. Full breastfeeding was recorded in 59.9% and the mixed lactation in 39.2%, bottle feeding 0.9% in the first 6 months of life. Achieving two years lactation was 23.4% among nursing mothers. High scoring of knowledge was recorded in 55% of women and 39.6% recorded moderate score. Positive community attitude was found in 86% of the sample. Lower percentage of full breastfeeding was found among mothers having their first child, high level of education, medium economic class, full time employment, women with husband with professional occupation, female gender babies and delivery with caesarean section under general anaesthesia. Conclusion Accepted level of knowledge is found in the majority of mothers, there is some improvement in the percentage of mothers in achieving the full breastfeeding may be due to the effect of the governmental protocol to encourage this natural practice. Still there is very low percentage of women that can achieve two years lactation that is recommended by the world health organization. Certain risk group can be identified.